The gender gap in bank credit access - de Andrés, Pablo; Gimeno, Ricardo; Mateos de Cabo, Ruth (Journal of Corporate Finance, 2021)
We use a sample of over 80,000 Spanish companies started by a sole entrepreneur between 2004 and 2014, and distinguish between male and female entrepreneurs demand for credit, credit approval ratio, and credit performance. We find that female entrepreneurs who start a business are less likely to ask for a loan. Of the female entrepreneurs requesting a credit, the probability of obtaining one in the founding year is significantly lower than their male peers in the same industry. This lower credit access disappears over the subsequent years, once the company has a track record of profits and losses. We also observe that women-led companies that receive a loan in the founding year are less likely to default as compared to men-led companies. This superior performance disappears for subsequent years, coinciding with the disappearance of the lower credit access. Taking all these results together, we rule out both taste-based discrimination and statistical discrimination in the credit industry, and point to the possible presence of double standards which might be a consequence of implicit (unconscious) discrimination.